Nowadays wood supplies from natural forest are decreasing. Many efforts had been done to overcome this problem. One of them was by developing plantation forest, however it has not optimized yet because of many problems. Lately wood supplies were fulfilled by community forest woods. One of them is cinnamon (Cinnamomum spp.). The research objective was to gain information on anatomical, physical, mechanical and chemical properties of C. burmanni Blume and to analyse its utilization based on thes - RAHAYU, Istie Sekartining; WAHYUDI, Imam; YOLANDA, Yoki Putra (Jurnal Ilmu dan Teknologi Hasil Hutan, 2012)
Nowadays wood supplies from natural forest are decreasing.  Many efforts had been done to overcome this problem. One of them was by developing plantation forest, however it has not optimized yet because of many problems. Lately wood supplies were fulfilled by community forest woods.  One of them is cinnamon (Cinnamomum spp.). The research objective was to gain information on anatomical, physical, mechanical and chemical properties of C. burmanni Blume and to analyse its utilization based on these properties. Wood samples used were three logs of 15 years old with 25 cm diameter. It showed that wood texture was fine, between sapwood and heartwood was not distinguished well. Specific gravity was 0.56, while MOE, MOR, and  compressive parallel to grain were 55.731 kg/cm2, 742 kg/cm2, and 392 kg/cm2, respectivelly. Solubility in ethanol benzene was 4.07%, cellulose content  was 48.53%, hemicellulose was 15.71% and lignin was 22.72%. Based on those properties, it could be recommended that C. burmanni wood was suitable enough for furniture, pulp, and light construction purposes.   Keywords :              community forest, Cinnanomum burmanii Blume, wood properties, wood utilization.